Foundational and practical aspects of resource analysis : 4th International Workshop, FOPARA 2015, London, UK, April 11, 2015. Revised selected papers /: 4th International Workshop, FOPARA 2015, London, UK, April 11, 2015. Revised selected papers. (2016) - Unknown
No abstract available